Examining acculturation model in an EFL context: learners’ attitudes towards target language accent vs. L1 accent - Sa’d, Seyyed Hatam Tamimi; Modirkhamene, Sima (Penerbit UKM, 2015)
According to Schumann‟s (1986) Acculturation Model, accent acts as a means of the learner‟s identification with either his/her mother tongue culture or the target language culture and affects his/her effort to learn English as a target Language. Taking up a critical stance, the present study, thus, aimed at investigating the role that learner attitudes and beliefs play in the language that learners adopt in their mother tongue (MT) or the target language (TL) (i.e., English) accent when speaking English in an instructed foreign language setting. The participants consisted of 213 Iranian male elementary EFL learners, aged 12 to 19 years. The data were elicited using a questionnaire consisting of both close-ended and open-ended questions, and were, furthermore, triangulated through focus-group interviews and class observations. The questionnaire required the participants to voice their opinions freely regarding the accent they assumed and preferred when using the target language and the reasons for their preferences. The findings revealed that 81.3% of the participants displayed strong preferences for the TL accent (i.e., English) while only 18.7% of the participants privileged speaking English with their MT accent. The rationale for the TL accent preference was found to be composed of nine categories with „intelligibility‟, „beauty and effectiveness of TL accent‟, and „resemblance to native speakers and avoidance of mockery‟ cited as the most primary reasons. On the other hand, the major reason for assuming a MT accent was to reveal one‟s identity through the MT accent. The study therefore highlighted the strong inclination among EFL learners to acculturate into the TL culture through assuming its accent.